Genetic susceptibility to rotavirus infection in Chinese children: a population-based case–control study. Issue 6 (3rd June 2021) - Wang, Jin-Xia; Chen, Li-Na; Zhang, Can-Jing; Zhou, Hong-Lu; Zhang, Yan-Hong; Zhang, Xin-Jiang; Hao, Zhi-Yong; Qiu, Chao; Ma, Jing-Chen; Zhao, Yu-Liang; Zhong, Weiming; Tan, Ming; et al.
ABSTRACT: Rotaviruses (RVs) are the leading cause of acute gastroenteritis in children, while histo-blood group antigens (HBGAs) are believed to be host attachment and susceptibility factors of RVs. A large case–control study nested in a population-based diarrhea surveillance targeting children <5 y of age was performed in rural Hebei province, north China. Saliva and serum samples were collected from all participants to determine HBGA phenotyping, FUT2 mutations, and RV IgG antibody titers. A logistic model was employed to assess the association between host HBGA secretor status and risk of RV infection. Among 235 RV cases and 680 non-diarrhea controls studied, 82.4% of participants were IgG positive by an average age of 77 months. Out of the 235 RV cases, 216 (91.9%) were secretors, whereas the secretor rate was 76.3% in the non-diarrhea controls, resulted in an adjusted OR of 3.0 (95%CI: 1.9–4.7, P < .0001) between the two groups. Our population-based case–control study indicated a strong association between host HBGA secretor status and risk of RV infection in Chinese children. The high prevalence of Lewis-positive secretor status strongly suggests that Chinese children may be genetically susceptible to current co-circulating RV strains, and thus, a universal childhood immunization program against RV disease should be successful in China.